2022
DOI: 10.3390/met12122007
|View full text |Cite
|
Sign up to set email alerts
|

Ti-20Nb-10Ta-5Zr Is Biosafe Alloy for Building of Ecofriendly Greenhouse Framework of New Generation

Abstract: The search for environmentally neutral construction materials is an important aim of science from the middle of the XX century. We elaborated the method of the smelting of the new alloy Ti-20Nb-10Ta-5Zr. The Ti-20Nb-10Ta-5Zr was a β-phase alloy with an ~550 MPa yield strength, an ~700 MPa of ultimate strength and >50 GPa Young’s modulus. The Ti-20Nb-10Ta-5Zr alloy did not generate reactive oxygen species in contradistinction to the widely used NiTi. The biocompatibility of Ti-20Nb-10Ta-5Zr was studied. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Currently, Ti-based alloys such as Ti-Nb-Zr-Ta-and/or Ti-Nb-Zr-Fe-based alloys are considered to be multifunctional alloys because they are commonly employed in various fields. As reported in a few studies, these applications are oriented to several engineering applications-in particular, aerospace and automotive [1][2][3][4] and agricultural applications [5]-and evidently also includes the biomedical field, where bone and dental implants are usually developed with such alloys [6,7]. As for biomedical application concerns, these alloys are remarkable because of their safe compositions with no significant toxic effects on the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, Ti-based alloys such as Ti-Nb-Zr-Ta-and/or Ti-Nb-Zr-Fe-based alloys are considered to be multifunctional alloys because they are commonly employed in various fields. As reported in a few studies, these applications are oriented to several engineering applications-in particular, aerospace and automotive [1][2][3][4] and agricultural applications [5]-and evidently also includes the biomedical field, where bone and dental implants are usually developed with such alloys [6,7]. As for biomedical application concerns, these alloys are remarkable because of their safe compositions with no significant toxic effects on the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Nb is also used to further ensure the stabilization of the β phase and improve the alloy’s processability during fabrication, while Ta enhances the mechanical properties and corrosion resistance of the resulting alloy [ 12 ]. Thus, it has been demonstrated that Ti alloys containing Mo, Nb, and/or Ta exhibit good biocompatibility and corrosion resistance in human body fluids without causing allergic reactions; at the same time, they have a low elastic modulus and overall superior mechanical properties, which make them suitable for applications as environmentally neutral construction materials and biomedical devices, more specifically orthopedic implants [ 8 , 10 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%